A framework for the integration of development and evolution: The forgotten legacy of James Meadows Rendel - Petino Zappala, María Alejandra (Studies in history and philosophy of science, 2024)
The historical challenges to bridge the gaps between developmental biology and population or statistical genetics under the explanatory dominance of the Modern Evolutionary Synthesis during the 20th century have been thoroughly documented. However, although several attempts to integrate these fields have been made, most have been deemed unsuccessful. As an example of those efforts, in this paper I discuss the work of James Meadows Rendel, a student of J. B. S. Haldane and disciple of Conrad Hal Waddington. I present his largely forgotten or unrecognized, but innovative, ideas about canalization and the role of development in phylogeny as a valuable piece to connect these fields that could still have important ramifications for today's evolutionary biology. In fact, it is expected that the legacy of J. M. Rendel will be rediscovered, and more importantly, incorporated and extended by future researchers, in light of the growth of evolutionary developmental biology in the last decades. What is more, this case offers a chance to critically revisit standard historiographies about the dichotomy between developmental and population genetics research frameworks in 20th century biology.